POLR3A-related hypomyelinating leukodystrophy: case report and literature review - A. F. Murtazina; T. V. Markova; A. A. Orlova; O. P. Ryzhkova; O. A. Shchagina; E. L. Dadali (Нервно-мышечные болезни)
Hypomyelinating leukodystrophies (HL) is a group of genetically heterogeneous neurodegenerative disorders characterized by a lack of brain myelin deposition. One of the most common autosomal recessive HL is HL type 7 caused by mutations in the POLR3A gene. We reported the first clinical case of a Russian patient with HL type 7.Proband is a 7‑year‑old patient with HL type 7. The diagnosis was confirmed by genealogy, neurological examination, brain magnetic resonance imaging and molecular genetic testing. Two compound‑heterozygous variants in the POLR3A gene were revealed in the patient. Each variant was described earlier in patients with variable clinical manifestations of neurodegenerative diseases. The peculiarities of clinical manifestations in our patient were the manifestation of the disease in the first year of life, the predominance of cerebellar symptoms, a movement limitation of the jaw, leading to worsening of dysarthria, a delay in the formation of permanent teeth and short stature. The course of the disease was moderate that could be explained by different effect of the variants in the POLR3A gene.POLR3A‑related disease is a group of clinically heterogeneous disorders manifesting from early childhood to adulthood and characterized by isolated spastic ataxia or ataxia combined with oligodontia and hypogonadotropic hypogonadism, isolated or complicated spastic paraplegia, as well as a combination of ataxia with extrapyramidal symptoms. Our case report demonstrates the complexity of diagnostic process in the absence of a peculiar clinical picture and specific changes in brain imaging.